Innovation capacity and economic development: China and India - Peilei Fan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Both China and India, the emerging giants in Asia, have achieved significant economic development in recent years. China has enjoyed a high annual GDP growth rate of 10 per cent and India has achieved an annual GDP growth rate of 6 per cent since 1981. Decomposing China and India's GDP growth from 1981 to 2004 into the three factors' contribution reveals that technology has contributed significantly to both countries' GDP growth, especially in the 1990s. R&D outputs (high-tech exports, service exports, and certified patents from USPTO) and inputs (R&D expenditure and human resources) further indicate that both countries have been very committed to R&D and their output is quite efficient. Both governments have played an essential role in transforming their national innovation systems so that they can be more adaptable to economic development. The main focus of their reforms has been to link the science sector with the business sector and to provide incentives for innovation activities. Balancing import of technology and indigenous R&D effort is another major theme. Innovation capability development has become more and more critical to the success of biofirms in India and China. Institutional factors have great influence on choice of innovation at the firm level, i.e., the decision at firm level in terms of indigenous R&D or import of technology. Nevertheless, limited financial resources and insufficiently qualified human resources remain two major challenges for domestic companies in both countries.
Keywords: O31; O3; L65; 330; China; India; innovation capability; domestic companies; ICT; biotech; Wirtschaftswachstum; Innovation; Technischer Fortschritt; Innovationspolitik; Biotechnologie; China; Indien